Defusing the Energy Trap: The Potential of Energy-Denominated Currencies to Facilitate a Sustainable Energy Transition - Sgouridis, Sgouris (Frontiers in Energy Research, 2014)
The universal adoption of fiat currencies and of the fractional reserve banking system coincided with access to and ability to utilize energy-dense fossil fuels leading to unprecedented rates of economic expansion. The depletion of economically recoverable fossil fuels though sets the stage for systemic crises as it is not adequately priced in the current market system. An energy-based system of exchange can be adopted in parallel to or in place of fiat currencies in order to facilitate a sustainable energy transition (SET) and mitigate the impacts of such crises. Energy-backed and energy-referenced currencies are discussed as two possible variants for their ability to realign the economic system to the thermodynamic limits of the physical world. The primary advantage of an energy-referenced currency over the current mechanisms for SET (like feed-in tariffs or carbon taxes) is realized with the decoupling of the monetary and credit functions, especially when debt is tied to future energy availability. While energy-backed (credit) systems can be easier to adopt on a regional scale, the full transition to an energy-reference currency system requires significant reform of the financial and monetary system although it would not radically disrupt the current economic valuations given the high degree of correlation between value and embodied energy.